Pumps - Black, Perry O. (Indianapolis : Theodore Audel &Co., 1970)
The purpose of this book is to aid in providing a better understanding of the fundamentals and operating principles of pumps, pump controls, and hydraulics. The applied principles and practical features of pumps and hydraulics are discussed in detail. Various installations, operations, and maintenance procedures are thoroughly covered in this book. Information contained will be of help to engineering students, junior engineers and designers, installation and maintenance technicians, shop mechanics, and others who are interested in technical education and self-advancement. With the aid of this book, the reader will be able to install and service pumps for nearly any application.
Includes index.
ne 07/05/2018
Loans
Keywords: Pumping machinery; Hydraulic machinery